Mengintegrasikan Pembiayaan Pendidikan Islam dengan Kebijakan Nasional dalam Mewujudkan SDGs No. 4 : Kajian QS. Al-Mujadallah Ayat 12-13, UU No. 20 Tahun 2003, dan Teori Human Capital - Khairunnisa Khairunnisa; Wedra Aprison; Andy Riski Pratama (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to examine the integration between Islamic education financing and national policies in order to achieve Sustainable Development Goal (SDGs) No. 4 on quality and inclusive education. Using an Islamic normative approach, national education policy analysis and human capital theory, this study explores the relationship between the financing principles in QS. Al-Mujadilah verses 12-13 and Law No 20 of 2003 on the National Education System. The research method used is descriptive qualitative with literature analysis techniques that include the study of Qur'anic interpretations, policy documents, and concepts of human capital theory. The results show that Islamic education financing, which is based on the principles of justice, equity, and sustainability, has great potential to support national education policies in improving access and quality of education in Indonesia. The principles of zakat, waqf and sadaqah as Islamic financial instruments can be optimized to close the gap in access to education, especially for marginalized groups. This research recommends a stronger synergy between Islamic financing principles, national education policy, and the human capital approach in order to realize inclusive and quality education in accordance with SDGs goal No. 4.